(untitled) (The Research of Medical Science Review, 2025)
Background: Infantile colic is a common condition characterized by excessive crying in infants, often without an identifiable cause. It can significantly impact both infant and parental well-being, prompting the need for effective treatments. Objective: To evaluate the efficacy of lactase enzyme (beta-galactosidase) in treating infantile colic in infants aged 1–6 months presenting to a tertiary care hospital. Study Design: A descriptive study. Place and duration of study. 6 months from july 2024 to dec 2024 MTI Hayatabad Medical Complex, Peshawar Methods: This descriptive study was conducted over six months in the outpatient department of a tertiary care pediatric unit. A total of 71 infants with infantile colic were enrolled based on the "3-3-3 rule." Lactase enzyme drops were administered before each feed. Efficacy was measured by reduction in crying time to <3 hours/day at two weeks, as reported by parents. Results: Out of 71 infants, 61 (85.9%) showed improvement in colic symptoms, while 10 (14.1%) had persistent symptoms. Efficacy was observed more frequently in urban residents, infants with middle socioeconomic status, and those on top feeding. Conclusion: Lactase enzyme supplementation is an effective intervention for infantile colic and significantly reduces parental stress and infant discomfort.